Privacy Protection Against Forced Wirebreaking Attempt by Law Enforcement Officials - Bagus Oktafian Abrianto; Dharma Setiawan Negara; Samuel Dharma Putra Nainggolan; Vivi Ayudya Permatasari (Sabtida, 2025)
The law permits coercive measures in law enforcement, one of which is telephone tapping. Initially, telephone tapping was closely linked to the protection of privacy as a human right; however, such protection can be limited when necessary and is regulated by law. In Indonesia, regulations governing telephone tapping remain fragmented, as several law enforcement agencies authorized to conduct telephone tapping regulate the mechanism independently through different legal frameworks. This situation has the potential to create legal uncertainty and raise concerns about the protection of citizens' privacy rights. This study uses normative legal research with a legal and conceptual approach. This study aims to analyze the authority of several state institutions to conduct telephone tapping and to examine the mechanisms governing telephone tapping to ensure the protection of the right to privacy as a human right in the law enforcement process